Exploring Students’ Speaking Anxiety Factors in an Online EFL Classroom - Iman Nugroho; Fauzi Miftakh; Yuna Tresna Wahyuna (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
Due to pandemic covid-19, the learning setting has changed from face-to-face to an online learning environment to prevent the further spread of infection. This change mostly affected the state of psychological, specifically anxiety issues. Specific anxiety called Foreign Language Anxiety (FLA) appears as anxiety affiliates with foreign language learning. Despite foreign language anxiety is evidenced to be hinder students’ achievements, there are only a few studies that have explored FLA in an online setting. Therefore, by using a case study, this research paper tried to investigate the factors of speaking anxiety of 5 students from different anxiety levels. These students were selected from a total of 30 students using the Foreign Language Anxiety Scale (FLCAS), which later be interviewed and asked to write a reflective journal. The result showed that some sources of each categorical factor (communication apprehension, test anxiety, fear of negative evaluation) can be classified as inter-lingual or intra-lingual factors. Moreover, some sources of factors have developed to new manifestations due to learning setting’ shifting. Additionally, as a part of communication apprehension, teachers’ bad teaching habits appeared as the most common factor to arise students’ speaking anxiety. Therefore, this study suggests teachers to evaluate their teaching habits, to reduce the influence of bad teaching habits on the students’ speaking anxiety.